Moon: prospective energy and material resources - Badescu, Viorel (Springer Berlin Heidelberg, 2012)
The Earth has limited material and energy resources. Further development of the humanity will require going beyond our planet for mining and use of extraterrestrial mineral resources and search of power sources. The exploitation of the natural resources of the Moon is a first natural step on this direction. Lunar materials may contribute to the betterment of conditions of people on Earth but they also may be used to establish permanent settlements on the Moon. This will allow developing new technologies, systems and flight operation techniques to continue space exploration.   In fact, a new branch of human civilization could be established permanently on Moon in the next century. But, meantime, an inventory and proper social assessment of Moon's prospective energy and material resources is required. This book investigates the possibilities and limitations of various systems supplying manned bases on Moon with energy and other vital resources. The book collects together recent proposals and innovative options and solutions. It is a useful source of condensed information for specialists involved in current and impending Moon-related activities and a good starting point for young researchers.